Invasive or non-invasive imaging for detecting high-risk coronary lesions?. (4th March 2017) - Patel, Kush; Tarkin, Jason; Serruys, Patrick W.; Tenekecioglu, Erhan; Foin, Nicolas; Zhang, Yao-Jun; Crake, Tom; Moon, James; Mathur, Anthony; Bourantas, Christos V.
ABSTRACT: Introduction : Advances in our understanding about atherosclerotic evolution have enabled us to identify specific plaque characteristics that are associated with coronary plaque vulnerability and cardiovascular events. With constant improvements in signal and image processing an arsenal of invasive and non-invasive imaging modalities have been developed that are capable of identifying these features allowing in vivo assessment of plaque vulnerability. Areas covered : This review article presents the available and emerging imaging modalities introduced to assess plaque morphology and biology, describes the evidence from the first large scale studies that evaluated the efficacy of invasive and non-invasive imaging in detecting lesions that are likely to progress and cause cardiovascular events and discusses the potential implications of the in vivo assessment of coronary artery pathology in the clinical setting. Expert commentary : Invasive imaging, with its high resolution, and in particular hybrid intravascular imaging appears as the ideal approach to study the mechanisms regulating atherosclerotic disease progression; whereas non-invasive imaging is expected to enable complete assessment of coronary tree pathology, detection of high-risk lesions, more accurate risk stratification and thus to allow a personalized treatment of vulnerable patients.